The Effects of Equivalence Ratio on Pressure Wave Development during Knocking Combustion (Journal of Scientific Research, 2018)
A knocking combustion in a one-dimensional constant volume reactor has been simulated with a detailed chemical kinetic mechanism of n-heptane premixed gases by using the compressible Navier-Stokes equations. This study focuses on the impact of the various equivalence ratios (0.6–1.4) in the pressure wave development during knocking combustion in an account of different initial temperature (600–900K). The result demonstrates the autoignition process in the end-gas region and explains the knocking phenomenon on different equivalence ratio. In an adiabatic wall condition, the largest knocking intensity occurs in equivalence ratio 1.4 whereas the lowest knocking intensity found in equivalence ratio 0.6. Regarding to initial temperatures, a strong peak of knocking is generated around 650K in all the equivalence ratios (0.8–1.4). However, yet a small perceptivity of knocking is found in around 750K for each equivalence ratio. In case of smaller equivalence ratios, a weak knocking occurs, which can be identified by the behavior of the pressure wave generation in the end-gas region.